2016
DOI: 10.1159/000441350
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Attentional Components in Elderly with Mild Neurocognitive Disorders Shown by the Attention Network Test

Abstract: Aims: Complex attention, serving as a main diagnostic item of mild neurocognitive disorders (NCD), has been reported to be susceptible to pathological ageing. This study aimed to evaluate the attention network functions in older adults with subtypes of NCD. Methods: 36 adults with NCD due to Alzheimer's disease (NCD-AD), 31 adults with NCD due to vascular disease (NCD-vascular) and 137 healthy controls were recruited. Attention Network Test (ANT) was conducted to assess the efficiency of alerting, orienting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 25 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…In this investigation, lower executive control efficacy was observed for patients ( Table 4 ). Notably, Lu et al ( 43 ) found that Chinese elderly with cerebrovascular disease had poorer executive attention effects than controls after correcting for general slowing. Similar phenomenon was replicated in subcortical stroke using modified ANT, and pathways connecting prefrontal areas to other regions were disrupted and displayed correlations with prolonged RT of executive control ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, lower executive control efficacy was observed for patients ( Table 4 ). Notably, Lu et al ( 43 ) found that Chinese elderly with cerebrovascular disease had poorer executive attention effects than controls after correcting for general slowing. Similar phenomenon was replicated in subcortical stroke using modified ANT, and pathways connecting prefrontal areas to other regions were disrupted and displayed correlations with prolonged RT of executive control ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the alerting network showed an age-related decline, with just one study reporting no age-related decline (Fernandez-Duque & Black, 2006). More specifically, one study focusing on the efficiency of attentional components in elderly people with mild neurocognitive disorders (NCD) showed that the NCD group was less efficient with respect to the executive control network, and had a slower processing speed compared to healthy elders (Lu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The other three major domains of cognitive function included the following 8 : (1) short-term memory measured by delayed recall of words and digit span backward (DSB), (2) attention measured by digit span forward (DSF) and trail making test part A (TMT-A) and (3) executive function measured by trail making test part B (TMT-B) and Chinese verbal fluency test (CVFT). The cerebrovascular risks were evaluated by CIRS 35 for the presence and severity of hypertension, hyperlipidaemia, heart diseases, diabetes mellitus, atrial fibrillation, and anaemia.…”
Section: Methodsmentioning
confidence: 99%
“…The two major subtypes of NCD described in the DSM-5 are due to vascular disease (NCD-vascular) or Alzheimer’s disease (NCD-AD) 2 . NCD-vascular and NCD-AD patients have shown group-wise differences with respect to mean RT 8 . There is also intra-individual variability due to advancing age, and this variability reflects the short-term fluctuations on cognitive tests.…”
Section: Introductionmentioning
confidence: 92%